Business Performance of MSMEs: an Analysis of the Effect of Entrepreneurial Orientation, Market Orientation, and Technology Orientation - Antony Sentoso; Tiara Plorist Sibarani; Evi Silvana Muchsinati (Universitas Negeri Semarang, 2024)
This study aims to evaluate the business performance of MSMEs in Batam City, focusing on the influence of entrepreneurial orientation, market orientation, and technology orientation, with the role of organizational culture as a mediating factor. The research methodology involves hypothesis testing through a structural equation model, with the research respondents being managers and owners of MSMEs in Batam who have been operating for more than one year. The sample was proportionally selected using purposive sampling, with a total of 260 MSMEs from various sectors in Batam City that met the criteria for analysis. The analysis results show that seven out of eight hypotheses have significant relationships, where entrepreneurial orientation and technology orientation have a positive impact on business performance. However, the hypothesis testing the influence of market orientation on business performance did not show a significant relationship. These findings highlight that in the context of MSMEs in Batam City, entrepreneurial and technology orientation play a more crucial role in enhancing business performance compared to market orientation.